Evaluation of Medical Error Status in Various Wards of Shohadaye Ashayer Hospital, Khorramabad, Iran - Reza Masoudi (Journal of Global Pharma Technology, 2016)
Medical errors are known as the most important challenges that healthcare systems in all countries areencountered to them. To provide security and safety for patient is one of the major items in the health care systems. Confessing medical errors imposed on patient and education system is found to be an important aspect of medical ethics and care in turn lowers incidence of errors. Given the importance of identifying and reporting occurred medical errors, the present research aimed to assess medical errors in hospital wards of Shohadaye Ashayer Hospital Khorramabad so that findings of this research can inspire us to incorporate medical errors as a very important subject in the curriculum of medical students and finally physicians can do best examination and treatment with minimal or no errors and inaccuracies. The present research is descriptive in nature which lasted from April to March 2015. Statistical population (subjects) included employees and supervisors, nurses, staffs, lab safety facilitator, pharmacy safety facilitator, surgery room personnel, equipment and personnel in the hospital wards, including the emergency department, men surgery, women surgery, operating room, orthopedics, internal medicine ward, neurology, laboratory room, surgery, infectious, ophthalmic, reception, pharmacy and CCU hospital in Shohadaye Ashayer Hospital- Khorramabad. Keywords: Medical Error, Shohadaye - Ashayer Hospital, Khorramabad, Iran.